Co- and counter-propagating wave effects in an absorbing medium. (February 2020) - Mishchenko, Michael I.; Yurkin, Maxim A.
Highlights: We revisit interference phenomena caused by pairs of co-propagating or counter-propagating transverse electromagnetic waves by letting the host medium be absorbing. We first consider plane waves in an unbounded medium. We then consider the superposition of plane and spherical waves in the context of far-field electromagnetic scattering by a particle. The physical similarity of the two scenarios is discussed. Abstract: In this semi-tutorial paper, we revisit the interference phenomena caused by pairs of co-propagating or counter-propagating transverse electromagnetic waves by letting the host medium be absorbing. We first consider plane waves in an unbounded medium, summarize the standing-wave solution of the Maxwell equations, and discuss specific effects caused by nonvanishing absorption. We then consider the superposition of plane and spherical waves in the context of far-field electromagnetic scattering by a particle. To this end we modify the classical Jones lemma by allowing nonzero absorption in the host medium and consider its most obvious consequences such as forward- and backscattering interference. The physical similarity of the two scenarios (superpositions of plane waves and superpositions of plane and spherical waves) is discussed.